Voting Behaviour and Political Communication - Abhishek Kaushal, Dr. Pavitra Shrivastava (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2025)
Political communication began with the earliest studies of democratic discourse by Aristotle and Plato. It is a subfield of communication and political science that is concerned with spread of information and how it influences politics and policy makers, the news media and citizens (Kaid and Bacha, 2008). Political actors refer to one another from competing positions in a temporized and organized space that is legally regulated concerning its goals, rhythm and legitimacy. Basically, there are main three actors of political communication, namely, Political Organizations; Media and Citizens (voters) (Mc Nair, 2017). Voting behaviour is a field of study concerned with the ways in which people tend to vote in public election and the reasons why they vote, as they do (Plano, Riggs & Robin, 1982). Present study has been incorporated to demarcate the individual influence of three vital actors of the political communication, namely, political messaging from political parties, audience (voters) and media. It is framed as, ‘Voting Behaviour and Political Communication’. Study adopted a descriptive survey research design. Bhopal was chosen as the universe of the study. Its geographical area is divided on the basis of its Legislative Assemblies. Almost equal sample was selected from each division. The sample of comprises of one sixty-eight (N=168) residents of Bhopal (MP), irrespective of the gender. A self-developed and standardized tool was used for data collection.